Assessment of Some Selected Traditional Weeding Tools for Safe Ergonomic Practices - Smruti Rekha Panigrahi; Nandita Bhattacharyya; Bijoylaxmi Bhuyan (Archives of Current Research International, 2025)
Weeding is a critical agricultural activity essential for maintaining crop health and optimizing yield by eliminating competition from unwanted plants. In India, manual weeding remains the predominant practice due to its cost-effectiveness and environmental sustainability compared to chemical herbicides. This study explores the use of various traditional hand tools for weeding, focusing on their design, the postures assumed during their use, and the ergonomic challenges faced by workers. Observational analysis and video documentation reveal that prolonged squatting, bending, and repetitive movements during manual weeding lead to significant physical strain and musculoskeletal issues among agricultural workers. The findings highlight the urgent need for ergonomic interventions to minimize worker discomfort and improve productivity. This paper provides insights into traditional weeding practices, their implications on worker health, and the potential benefits of redesigning tools to enhance safety, comfort, and efficiency in agricultural settings.